Guidelines for Transferring Residential Courses into Web - Tüzün, Hakan; Çınar, Murat (International Review of Research in Open and Distributed Learning, 2016)
This study shared unique design experiences by examining the process of transferring residential courses to the Web, and proposed a design model for individuals who want to transfer their courses into this environment. The formative research method was used in the study, and two project teams’ processes of putting courses, which were being taught in classrooms at the time, on the Web were examined in depth to reveal and confirm the components of the design model. The participants were 13 instructional designers. In addition to the logbooks kept by the designers, individual and focus group interview techniques were employed in the data-gathering process. Two researchers analyzed the data concurrently using content analysis. The logbooks and the focus-group interviews were used for model formation, and the individual interviews to confirm the components of the model. Based on the findings from the two design cases, the experience-based e-course design model consisting of seven basic stages including forming design team, preliminary search, analysis, instructional and technical design, integration, tests, and improvements was proposed. It is considered that sustaining Web-based course design efforts within this model will enable both implementing the design process more effectively, and the Web-based course obtained at the end of the process to have higher quality.